Effect sintering temperature on silica production using rice husk from Pasir Tumboh, Kelantan - Ahmad, Sufizar; Isamudin, Muhammad Ikhwan; Muslem, Muhammad Firdaus (Research Progress in Mechanical and Manufacturing Engineering, 2023)
This paper presents was to study the physical properties of the samples ceramic water filter in different sintering temperature that produce high silica content which in crystalline to reduce water pollution and agricultural waste. Rice husk ash from Pasir Tumboh, Kelantan divided by composition which 45wt%, 50wt%, 55wt%, 60wt% and 65wt% and each of the ash were mixture with Polyethylene Glycol (PEG) by 1 wt%. The mixture material was compacted by hydraulic press machine and going through with thermal treatment to produce the filter samples. The filter samples were sintered at temperature 900°C, 950°C, 1000°C, 1050°C and 1100°C in order to observer the effect of sintering temperature on the ceramic filter samples. Density and porosity test plus water absorption test was perform in order to evaluate the physical properties of the sample. The results show that the filter composition 45wt% have lowest percentage of water absorption and apparent porosity plus highest bulk density.